Impact of post-deposition annealing on interfacial chemical bonding states between AlGaN and ZrO2 grown by atomic layer deposition - Ye, Gang (2015)
The effect of post-deposition annealing on chemical bonding states at interface between Al0.5Ga0.5N and ZrO2 grown by atomic layer deposition (ALD) is studied by angle-resolved x-ray photoelectron spectroscopy and high-resolution transmission electron microscopy. It has been found that both of Al-O/Al 2p and Ga-O/Ga 3d area ratio decrease at annealing temperatures lower than 500 °C, which could be attributed to “clean up” effect of ALD-ZrO2 on AlGaN. Compared to Ga spectra, a much larger decrease in Al-O/Al 2p ratio at a smaller take-off angle θ is observed, which indicates higher effectiveness of the passivation of Al-O bond than Ga-O bond through “clean up” effect near the interface. However, degradation of ZrO2/AlGaN interface quality due to re-oxidation at higher annealing temperature (>500 °C) is also found. The XPS spectra clearly reveal that Al atoms at ZrO2/AlGaN interface are easier to get oxidized as compared with Ga atoms.